A composite viscosity reducing agent and its oil recovery viscosity reducing process
By using composite viscosity reducing agents, including amphiphilic copolymers, fatty alcohol polyoxyethylene ether sodium sulfonate and modified nanosilica, combined with hydraulic cavitation treatment, the existing heavy oil viscosity reducing agents have insufficient temperature resistance and salt resistance in high-temperature and high-salt environments, and efficient viscosity reduction effect and stability have been achieved.
Patent Information
- Application Number
- CN202411719608.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The existing heavy oil viscosity reducing agents show poor temperature resistance and insufficient salt resistance in high-temperature and high-salt environments, and are complex in composition, high cost, and poor viscosity reduction effect.
The composite viscosity reducing agent is used, consisting of amphiphilic copolymer, fatty alcohol polyoxyethylene ether sodium sulfonate and modified nanosilica. Through specific proportional combination and hydraulic cavitation treatment, the viscosity reduction effect is improved and adapted to the complex reservoir environment.
It achieves good viscosity reduction effect in high temperature and high salt environments, has excellent temperature resistance and stability, reduces the viscosity of crude oil, and is suitable for complex reservoir environments.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to a composite viscosity reducer and an oil recovery viscosity reducing process thereof, belonging to the technical field of petrochemical industry. Background Art
[0002] Heavy oil has a high content of colloid asphaltene, and has the characteristics of high density, high viscosity and poor flow. In order to improve the flowability of heavy oil, the fluidity of heavy oil must be improved. The key to improving the fluidity of heavy oil is to reduce the viscosity and freezing point of heavy oil. As long as the viscosity of heavy oil is reduced, its freezing point will also be reduced. Therefore, at present, heavy oil viscosity reduction is almost the basic idea of improving the flowability of heavy oil. The use of viscosity reducers for viscosity reduction has become the main method of heavy oil viscosity reduction due to its low cost and convenient construction.
[0003] The viscosity reducers mainly include microbial viscosity reducers, water-soluble emulsified viscosity reducers, and oil-soluble emulsified viscosity reducers. Among them, microorganisms are not suitable for heavy oils with high temperature, high mineralization, and heavy metal ions because they have harsh adaptability and strong selectivity for formation conditions, so they are not easy to promote and apply. There are mainly three types of materials in emulsified viscosity reducers. One is surfactants. Non-ionic surfactants have poor temperature resistance. When the temperature is higher than its cloud point, phase separation will occur, which reduces the solubility of surfactants. Anionic surfactants have strong temperature resistance but poor salt resistance, which limits their application in heavy oil emulsification and viscosity reduction. The second is high molecular polymers, which have weak penetration ability, are easy to entangle between molecules, and are difficult to adsorb on the surface of heavy oil. The third is organic solvents, which mainly rely on organic solvents to dissolve asphalt, paraffin and other substances in heavy oil. The solubilization capacity of organic solvents is limited, and the amount used is large, which will also bring certain troubles to the later refining process of heavy oil.
[0004] Chinese invention patent CN201110446042.4 discloses a salt-resistant and heat-resistant heavy oil emulsifier viscosity reducer, which is composed of sulfonate anionic surfactant, disodium sulfosuccinate monolaurate, disodium nonylphenol polyoxyethylene ether sulfosuccinate monoester, polyoxyethylene ether ester salt, nonylphenol polyoxyethylene polyoxypropylene alcohol ether block copolymer, carboxymethyl polyoxyethylene ether, organic amide polyoxyethylene ether, polyoxyethylene polyoxypropylene polyethylene polyamine, sulfonate polyacrylamide, nonionic fluorocarbon surfactant, modified nano additive, alkaline additive and water. The salt resistance of this salt-resistant and heat-resistant heavy oil emulsifier viscosity reducer reaches 24×10 4 mg / L, but its temperature resistance is only 150℃, and its composition is complex, the price is expensive, and the viscosity reduction effect is average. Summary of the invention
[0005] In order to solve the above problems, a composite viscosity reducer and an oil recovery viscosity reducing process thereof are provided. The composite viscosity reducer is prepared by compounding an amphiphilic copolymer, sodium polyoxyethylene fatty alcohol ether sulfonate and modified nano-silica in a specific ratio to improve the viscosity reducing effect. The sodium polyoxyethylene fatty alcohol ether sulfonate can interact with the colloid asphaltene molecules and has a solvation effect and a solubilization effect to effectively reduce the viscosity. In combination with a hydraulic cavitation transducer, the sodium polyoxyethylene fatty alcohol ether sulfonate can be fully mixed and emulsified with the crude oil and the crude oil can be heated to further improve the oil recovery viscosity reducing effect. The composite viscosity reducer has good temperature resistance and can adapt to complex reservoir environments.
[0006] According to one aspect of the present application, a composite viscosity reducer is provided, comprising an amphiphilic copolymer, sodium fatty alcohol polyoxyethylene ether sulfonate, modified nano-silica and water; wherein the composite viscosity reducer comprises 0.5-5wt% of the amphiphilic copolymer, 0.05-2wt% of sodium fatty alcohol polyoxyethylene ether sulfonate, 5-15wt% of the modified nano-silica and the remainder of water.
[0007] Optionally, the method for preparing the amphiphilic copolymer comprises the following steps:
[0008] S1: dissolving acrylamide, N,N-dimethylacrylamide and N-acryloylmorpholine in water, passing nitrogen to remove oxygen, adding initiator azobisisobutylamidine hydrochloride, heating and initiating polymerization reaction for 8 to 10 hours;
[0009] S2: the product obtained in step S1 is precipitated with alcohol for 3 to 5 times, dissolved in a small amount of water, precipitated with alcohol, and then vacuum dried at 40 to 50° C. to obtain an amphiphilic copolymer.
[0010] Specifically, acrylamide, N,N-dimethylacrylamide and N-acryloylmorpholine are used as monomers, and acrylamide is combined with dimethylacrylamide and acryloylmorpholine to obtain a terpolymer through free radical copolymerization in aqueous solution. Acrylamide is a monomer with a strong polar group. Its introduction can increase the ability to form strong polar hydrogen bonds with colloid asphaltene, thereby destroying the aggregate structure originally existing in the crude oil, releasing light components, and thus reducing the viscosity of the crude oil; N,N-dimethylacrylamide has hydrophilic and lipophilic amphiphilic properties, is easily soluble in water and a variety of organic solvents, and has a similar structure to acrylamide, and the two are easy to copolymerize; N-acryloylmorpholine has good solubility and biocompatibility, and has a certain similarity in structure to acrylamide and N,N-dimethylacrylamide. The terpolymer obtained by copolymerization has high interfacial activity, which is conducive to achieving crude oil viscosity reduction.
[0011] Optionally, the preparation method of the modified nano-silicon dioxide comprises the following steps:
[0012] S01: dissolving 3-(methacryloyloxy)propyltrimethoxysilane in toluene, adding the mixture to the nano-silicon dioxide aqueous dispersion, subjecting the mixture to ultrasonic treatment at 60-65°C for 45-60 minutes, and stirring the mixture for 2-3 hours to obtain a modified nano-silicon dioxide dispersion; the pH value of the nano-silicon dioxide aqueous dispersion is 4-5;
[0013] S02: centrifuging the obtained modified nano-silica dispersion, repeatedly washing with ethanol, and then vacuum drying to obtain modified nano-silica.
[0014] Specifically, the modified nano-silica has an extremely large specific surface area and an extremely strong adsorption capacity, and can adsorb the amphiphilic copolymer on the surface, thereby improving the dispersion ability of the amphiphilic copolymer in crude oil, thereby improving the viscosity reduction effect.
[0015] Optionally, the molar ratio of acrylamide, N,N-dimethylacrylamide and N-acryloylmorpholine is (12-15): (3-4): (2-3); the weight of the initiator is 0.5%-1% of the total weight of acrylamide, N,N-dimethylacrylamide and N-acryloylmorpholine.
[0016] Optionally, the mass ratio of the 3-(methacryloyloxy)propyltrimethoxysilane to the nano-silicon dioxide is 1:(10-15).
[0017] Optionally, the preparation method of sodium fatty alcohol polyoxyethylene ether sulfonate comprises the following steps:
[0018] S001 Add distilled water to a high temperature and high pressure reactor, then add sodium sulfate, sodium sulfite, sodium bisulfite and sodium bisulfate of fatty alcohol polyoxyethylene ether, stir evenly, and react for 6-8 hours;
[0019] The materials in the S002 reactor are cooled to room temperature, and the reaction mixture is first dissolved with isopropanol, and dichloromethane is added to assist in dissolution, and then suction filtration, desalination, and solvent evaporation are performed in sequence to obtain sodium fatty alcohol polyoxyethylene ether sulfonate.
[0020] Optionally, the mass ratio of the sodium sulfite, sodium bisulfite and sodium bisulfate is (4-5):1:(0.05-0.1); the mass ratio of the sodium sulfite to sodium fatty alcohol polyoxyethylene ether sulfate is 1:(0.7-0.9).
[0021] Optionally, in step S001, the reaction temperature is 150-170° C., and the reaction pressure is 0.5-0.6 MPa.
[0022] Specifically, sodium fatty alcohol polyoxyethylene ether sulfonate interacts with gum and asphaltene molecules. The O atoms in the sulfonic acid group and the O atoms in the alkoxy group have strong hydrogen bonding ability and penetration and dispersion effect to enter between the gum and asphaltene flaky molecules, and form stronger hydrogen bonds with polar groups such as -OH and -NH2 in the gum and asphaltene, thereby reducing the viscosity; the longer alkyl chains in sodium fatty alcohol polyoxyethylene ether sulfonate fully stretch around the gum and asphaltene aggregates to form a viscosity reducer solvation layer to prevent the gum and asphaltene from re-aggregating; the well-dispersed gum and asphaltene molecules have a good solubilizing effect with the alkyl chains in the sodium fatty alcohol polyoxyethylene ether sulfonate molecules, reducing the number of molecules of gum and asphaltene aggregates, and the combined effect reduces the viscosity of crude oil.
[0023] Specifically, the sodium fatty alcohol polyoxyethylene ether sulfonate has strong salt resistance and is suitable for high-temperature and high-salt oil reservoirs.
[0024] Optionally, the preparation method of the composite viscosity reducer comprises the following steps:
[0025] Step 1: dissolve the amphiphilic copolymer in a small amount of water, add modified nano-silica, and ultrasonicate at 40-60℃ for 30-45min;
[0026] Step 2: Continue to add sodium fatty alcohol polyoxyethylene ether sulfonate and water, and stir evenly to obtain the composite viscosity reducer.
[0027] According to another aspect of the present application, there is also provided an oil recovery viscosity reduction process using the composite viscosity reducer, comprising the following steps:
[0028] (1) subjecting the composite viscosity reducer to hydraulic cavitation treatment for 1 to 3 times;
[0029] (2) After the composite viscosity reducer treated by hydraulic cavitation is fully mixed with the crude oil, the hydraulic cavitation treatment is performed again for 5 to 10 times;
[0030] The inlet temperature of the hydrodynamic cavitation treatment is 40-80° C., and the inlet pressure is 0.7-0.9 MPa.
[0031] The beneficial effects of this application include but are not limited to:
[0032] 1. According to the composite viscosity reducer of the present application, the amphiphilic copolymer, sodium fatty alcohol polyoxyethylene ether sulfonate, and modified nano-silica are compounded in a specific ratio. By compounding the amphiphilic copolymer with the modified nano-silica, the modified nano-silica has an ultra-large specific surface area and ultra-strong adsorption capacity, and the amphiphilic copolymer can be adsorbed on the surface, thereby improving the dispersion ability of the amphiphilic copolymer in crude oil, thereby improving the viscosity reduction effect; the sodium fatty alcohol polyoxyethylene ether sulfonate can interact with the colloid asphaltene molecules, and has a solvation effect and a solubilization effect, effectively achieving viscosity reduction, and in conjunction with a hydraulic cavitation transducer, the sodium fatty alcohol polyoxyethylene ether sulfonate can be fully mixed and emulsified with the crude oil, and the crude oil is heated, further improving the oil displacement viscosity reduction effect, and the composite viscosity reducer has good temperature resistance and can adapt to complex reservoir environments.
[0033] 2. According to the composite viscosity reducer of the present application, acrylamide, N,N-dimethylacrylamide and N-acryloylmorpholine are used as monomers, and acrylamide is combined with dimethylacrylamide and acryloylmorpholine to obtain a terpolymer through free radical copolymerization in aqueous solution. Acrylamide is a monomer with a strong polar group. Its introduction can increase the ability to form strong polar hydrogen bonds with colloid asphaltene, thereby destroying the aggregate structure originally existing in crude oil, releasing light components, and thus reducing the viscosity of crude oil; N,N-dimethylacrylamide has hydrophilic and lipophilic amphiphilic properties, is easily soluble in water and a variety of organic solvents, and has a similar structure to acrylamide, and the two are easy to copolymerize; N-acryloylmorpholine has good solubility and biocompatibility, and has a certain similarity in structure to acrylamide and N,N-dimethylacrylamide. The terpolymer obtained by copolymerization has high interfacial activity, which is conducive to achieving crude oil viscosity reduction; the present application makes specific restrictions on the ratio of raw materials and reaction conditions to ensure the interfacial activity of the copolymer to achieve a better viscosity reduction effect.
[0034] 3. According to the composite viscosity reducer of the present application, nano-silicon dioxide has a reactive double bond structure, can be used for free radical polymerization, and has a micro-nano structured surface that easily causes fluid slippage, thereby reducing the friction force of the fluid layer during relative motion, and can also react with wax in crude oil to reduce viscosity; the present application makes specific restrictions on the preparation method of nano-silicon dioxide to ensure the modification effect.
[0035] 4. According to the composite viscosity reducer of the present application, sodium fatty alcohol polyoxyethylene ether sulfonate is compounded with an amphiphilic copolymer. The amphiphilic copolymer reduces viscosity based on interfacial active emulsification. Sodium fatty alcohol polyoxyethylene ether sulfonate interacts with colloid and asphaltene molecules. The O atoms in the sulfonic acid group and the O atoms in the alkoxy group have strong hydrogen bonding ability and penetration and dispersion effect to enter between the colloid and asphaltene flake molecules, and form stronger hydrogen bonds with polar groups such as -OH and -NH2 in the colloid and asphaltene to reduce viscosity; the longer alkyl chains in sodium fatty alcohol polyoxyethylene ether sulfonate fully extend around the colloid and asphaltene aggregates to form a viscosity reducer solvation layer to prevent the colloid and asphaltene from re-aggregating; the dispersed colloid and asphaltene molecules have a good solubilizing effect with the alkyl chains in the sodium fatty alcohol polyoxyethylene ether sulfonate molecules, reducing the number of molecules of colloid and asphaltene aggregates, and the combined effect reduces the viscosity of crude oil; sodium fatty alcohol polyoxyethylene ether sulfonate and the amphiphilic copolymer cooperate to achieve crude oil viscosity reduction.
[0036] 5. According to the composite viscosity reducer oil production viscosity reduction process of the present application, hydraulic cavitation is combined with a specific composite viscosity reducer, the composite viscosity reducer is treated by hydraulic cavitation and then mixed evenly with crude oil, and then treated by hydraulic cavitation again to achieve a good viscosity reduction effect. DETAILED DESCRIPTION
[0037] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0038] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in this patent are for demonstration purposes only.
[0039] Example 1
[0040] Preparation of amphiphilic copolymers:
[0041] S1: dissolving acrylamide, N,N-dimethylacrylamide and N-acryloylmorpholine in water, passing nitrogen to remove oxygen, adding initiator azobisisobutylamidine hydrochloride, the molar ratio of acrylamide, N,N-dimethylacrylamide and N-acryloylmorpholine is 12:3:2; the weight of the initiator is 0.5% of the total weight of acrylamide, N,N-dimethylacrylamide and N-acryloylmorpholine, heating to 50°C, and initiating polymerization reaction for 8 hours;
[0042] S2: the product obtained in step S1 is precipitated with alcohol three times, dissolved in a small amount of water, precipitated with alcohol, and then vacuum dried at 40° C. to obtain an amphiphilic copolymer;
[0043] Preparation method of modified nano-silica:
[0044] S01: 3-(methacryloyloxy)propyltrimethoxysilane was dissolved in toluene, added into the nano-silica aqueous dispersion, subjected to ultrasonic treatment at 60°C for 45 minutes, and stirred for reaction for 2 hours to obtain a modified nano-silica dispersion; the pH of the nano-silica aqueous dispersion was 4, and the mass ratio of 3-(methacryloyloxy)propyltrimethoxysilane to silica was 1:10;
[0045] S02 centrifuging the obtained modified nano-silicon dioxide dispersion, repeatedly washing with ethanol and then vacuum drying to obtain modified nano-silicon dioxide;
[0046] Preparation method of sodium fatty alcohol polyoxyethylene ether sulfonate:
[0047] S001 Add distilled water to the high temperature and high pressure reactor, then add sodium sulfate, sodium sulfite, sodium bisulfite and sodium bisulfate, the mass ratio of sodium sulfite, sodium bisulfite and sodium bisulfate is 4:1:0.05, the mass ratio of sodium sulfite to sodium sulfate is 1:0.7, after stirring evenly, the reaction temperature is 150°C, the reaction pressure is 0.5MPa; react for 6h;
[0048] The materials in the S002 reactor are cooled to room temperature, and the reaction mixture is first dissolved with isopropanol, and dichloromethane is added to assist in dissolution, and then suction filtration, desalination, and solvent evaporation are performed in sequence to obtain sodium fatty alcohol polyoxyethylene ether sulfonate.
[0049] Preparation of composite viscosity reducer 1#:
[0050] Step 1: dissolve the amphiphilic copolymer in a small amount of water, add modified nano-silica, and ultrasonicate at 40°C for 30 min;
[0051] Step 2: Continue to add sodium fatty alcohol polyoxyethylene ether sulfonate and water, stir evenly, and obtain the composite viscosity reducer, which includes 0.5wt% of amphiphilic copolymer, 0.05wt% of sodium fatty alcohol polyoxyethylene ether sulfonate, 5wt% of modified nano-silica and the balance of water.
[0052] Composite viscosity reducer 1# oil production viscosity reduction process:
[0053] (1) subjecting composite viscosity reducer 1# to a hydrodynamic cavitation treatment once;
[0054] (2) After the hydraulic cavitation treatment, the composite viscosity reducer 1# was fully mixed with the crude oil and then subjected to hydraulic cavitation treatment for 5 times; the inlet temperature of the hydraulic cavitation treatment was 40°C and the inlet pressure was 0.7 MPa.
[0055] Example 2
[0056] Preparation of amphiphilic copolymers:
[0057] S1: dissolving acrylamide, N,N-dimethylacrylamide and N-acryloylmorpholine in water, passing nitrogen to remove oxygen, adding initiator azobisisobutylamidine hydrochloride, the molar ratio of acrylamide, N,N-dimethylacrylamide and N-acryloylmorpholine is 15:4:3; the weight of the initiator is 1% of the total weight of acrylamide, N,N-dimethylacrylamide and N-acryloylmorpholine, heating to 60°C, and initiating polymerization for 10 hours;
[0058] S2: the product obtained in step S1 is precipitated with alcohol five times, dissolved in a small amount of water, precipitated with alcohol, and then vacuum dried at 50° C. to obtain an amphiphilic copolymer;
[0059] Preparation method of modified nano-silica:
[0060] S01 3-(methacryloyloxy)propyltrimethoxysilane was dissolved in toluene, added to the nano-silica aqueous dispersion, ultrasonicated at 65°C for 60 minutes, stirred and reacted for 3 hours to obtain a modified nano-silica dispersion; the pH of the nano-silica aqueous dispersion was 5, and the mass ratio of 3-(methacryloyloxy)propyltrimethoxysilane to silica was 1:15;
[0061] S02 centrifuging the obtained modified nano-silicon dioxide dispersion, repeatedly washing with ethanol and then vacuum drying to obtain modified nano-silicon dioxide;
[0062] Preparation method of sodium fatty alcohol polyoxyethylene ether sulfonate:
[0063] S001 Add distilled water to the high temperature and high pressure reactor, then add sodium sulfate, sodium sulfite, sodium bisulfite and sodium bisulfate, the mass ratio of sodium sulfite, sodium bisulfite and sodium bisulfate is 5:1:0.1, the mass ratio of sodium sulfite to sodium sulfate is 1:0.9, after stirring evenly, the reaction temperature is 170°C, the reaction pressure is 0.6MPa; react for 8h;
[0064] The materials in the S002 reactor are cooled to room temperature, and the reaction mixture is first dissolved with isopropanol, and dichloromethane is added to assist in dissolution, and then suction filtration, desalination, and solvent evaporation are performed in sequence to obtain sodium fatty alcohol polyoxyethylene ether sulfonate.
[0065] Preparation of composite viscosity reducer 2#:
[0066] Step 1: dissolve the amphiphilic copolymer in a small amount of water, add modified nano-silica, and ultrasonicate at 60°C for 45 min;
[0067] Step 2: Continue to add sodium fatty alcohol polyoxyethylene ether sulfonate and water, stir evenly, and obtain the composite viscosity reducer, which includes 5wt% of amphiphilic copolymer, 2wt% of sodium fatty alcohol polyoxyethylene ether sulfonate, 15wt% of modified nano-silica and the balance of water.
[0068] Composite viscosity reducer oil recovery viscosity reduction process:
[0069] (1) The composite viscosity reducer 2# was subjected to hydrodynamic cavitation treatment three times;
[0070] (2) After the hydraulic cavitation treatment, the composite viscosity reducer 2# was fully mixed with the crude oil and then subjected to hydraulic cavitation treatment 10 times; the inlet temperature of the hydraulic cavitation treatment was 80°C and the inlet pressure was 0.9 MPa.
[0071] Example 3
[0072] Preparation of amphiphilic copolymers:
[0073] S1: dissolving acrylamide, N,N-dimethylacrylamide and N-acryloylmorpholine in water, passing nitrogen to remove oxygen, adding initiator azobisisobutylamidine hydrochloride, the molar ratio of acrylamide, N,N-dimethylacrylamide and N-acryloylmorpholine is 14:3:3; the weight of the initiator is 0.5% of the total weight of acrylamide, N,N-dimethylacrylamide and N-acryloylmorpholine, heating to 50 degrees Celsius, and initiating polymerization reaction for 8 hours;
[0074] S2: the product obtained in step S1 is precipitated with alcohol four times, dissolved in a small amount of water, precipitated with alcohol, and then vacuum dried at 50° C. to obtain an amphiphilic copolymer;
[0075] Preparation method of modified nano-silica:
[0076] S01 3-(methacryloyloxy)propyltrimethoxysilane was dissolved in toluene, added to the nano-silica aqueous dispersion, ultrasonicated at 60°C for 50 minutes, stirred and reacted for 3 hours to obtain a modified nano-silica dispersion; the pH of the nano-silica aqueous dispersion was 5, and the mass ratio of 3-(methacryloyloxy)propyltrimethoxysilane to silica was 1:10;
[0077] S02 centrifuging the obtained modified nano-silicon dioxide dispersion, repeatedly washing with ethanol and then vacuum drying to obtain modified nano-silicon dioxide;
[0078] Preparation method of sodium fatty alcohol polyoxyethylene ether sulfonate:
[0079] S001 Add distilled water to the high temperature and high pressure reactor, then add sodium sulfate, sodium sulfite, sodium bisulfite and sodium bisulfate, the mass ratio of sodium sulfite, sodium bisulfite and sodium bisulfate is 5:1:0.05, the mass ratio of sodium sulfite to sodium sulfate is 1:0.8, after stirring evenly, the reaction temperature is 160°C, the reaction pressure is 0.6MPa; react for 6h;
[0080] The materials in the S002 reactor are cooled to room temperature, and the reaction mixture is first dissolved with isopropanol, and dichloromethane is added to assist in dissolution, and then suction filtration, desalination, and solvent evaporation are performed in sequence to obtain sodium fatty alcohol polyoxyethylene ether sulfonate.
[0081] Preparation of composite viscosity reducer 3#:
[0082] Step 1: dissolve the amphiphilic copolymer in a small amount of water, add modified nano-silica, and ultrasonicate at 60°C for 45 min;
[0083] Step 2: Continue to add sodium fatty alcohol polyoxyethylene ether sulfonate and water, stir evenly, and obtain the composite viscosity reducer, which includes 2wt% of amphiphilic copolymer, 2wt% of sodium fatty alcohol polyoxyethylene ether sulfonate, 10wt% of modified nano-silica and the balance of water.
[0084] Composite viscosity reducer oil recovery viscosity reduction process:
[0085] (1) The composite viscosity reducer 3# was subjected to hydrodynamic cavitation treatment three times;
[0086] (2) After the hydraulic cavitation treatment, the composite viscosity reducer 3# was fully mixed with the crude oil and then subjected to hydraulic cavitation treatment for 8 times; the inlet temperature of the hydraulic cavitation treatment was 60°C and the inlet pressure was 0.9 MPa.
[0087] Example 4
[0088] The difference between Example 4 and Example 3 is that the step of subjecting the composite viscosity reducer to hydrodynamic cavitation treatment is not included.
[0089] Comparative Example 1
[0090] The difference between Comparative Example 1 and Example 3 is that unmodified nano-silicon dioxide is added, and the rest are the same.
[0091] Comparative Example 2
[0092] The difference between Comparative Example 2 and Example 3 is that the composite viscosity reducer includes 4 wt % of the amphiphilic copolymer, 10 wt % of the modified nano-silica and the balance of water, but does not include sodium fatty alcohol polyoxyethylene ether sulfonate, and the rest are the same.
[0093] Comparative Example 3
[0094] The difference between Comparative Example 3 and Example 3 is that in the preparation process of the amphiphilic copolymer, the molar ratio of acrylamide, N,N-dimethylacrylamide and N-acryloylmorpholine is 1:1:1. The rest are the same.
[0095] Comparative Example 4
[0096] The difference between Comparative Example 4 and Example 3 is that in the preparation method of modified nano-silica, the mass ratio of 3-(methacryloyloxy)propyltrimethoxysilane to silicon dioxide is 1:1, and the rest are the same.
[0097] Experimental Example 1: Viscosity Reduction Evaluation
[0098] A crude oil sample from a block of Shengli Oilfield was selected, and the crude oil viscosity was 4690 mPa·s at 50°C. The composite viscosity reducers prepared in Examples 1 to 4, the composite viscosity reducers prepared in Comparative Examples 1 to 4, and similar products on the market were evaluated for viscosity reduction effects. The evaluation method was based on Q / SH10201519-2016 "General Technical Conditions for Viscous Oil Viscosity Reducers", and the test results are shown in Table 1.
[0099] Table 1 Viscosity reduction test results of viscosity reducer
[0100]
[0101] Experimental Example 2: Temperature Resistance Test
[0102] A crude oil sample from a block of Shengli Oilfield was selected. The crude oil viscosity was 4690 mPa·s at 50°C. The composite viscosity reducers prepared in Examples 1 to 4, the composite viscosity reducers prepared in Comparative Examples 1 to 4, and similar commercial products were evaluated for viscosity reduction effects at different temperatures. The results are shown in Table 2.
[0103] Table 2 Temperature resistance test results
[0104]
[0105] Experimental Example 3: Stability Test
[0106] A crude oil sample from a block of Shengli Oilfield was selected. The crude oil viscosity was 4690 mPa·s at 50°C. The composite viscosity reducers prepared in Examples 1 to 4, the composite viscosity reducers prepared in Comparative Examples 1 to 4, and similar commercial products were evaluated for viscosity reduction effects at different storage times. The results are shown in Table 3.
[0107] Table 3 Stability test results
[0108]
[0109] The present application provides a composite viscosity reducer and an oil production viscosity reducing process thereof, wherein the specific composite viscosity reducer is subjected to hydraulic cavitation treatment, the viscosity reduction rate is greatly improved, and the composite viscosity reducer has excellent temperature resistance and stability, so as to cooperate with the hydraulic cavitation treatment.
[0110] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.
Claims
1. A composite viscosity reducer, characterized in that: The invention comprises an amphiphilic copolymer, sodium fatty alcohol polyoxyethylene ether sulfonate, modified nano silicon dioxide and water; wherein the composite viscosity reducer comprises 0.5 to 5wt% of the amphiphilic copolymer, 0.05 to 2wt% of sodium fatty alcohol polyoxyethylene ether sulfonate, 5 to 15wt% of the modified nano silicon dioxide and the balance of water; and the preparation method of the amphiphilic copolymer comprises the following steps: S1: dissolving acrylamide, N,N-dimethylacrylamide and N-acryloylmorpholine in water, passing nitrogen to remove oxygen, adding initiator azobisisobutylamidine hydrochloride, heating and initiating polymerization reaction for 8 to 10 hours; S2: the product obtained in step S1 is precipitated with alcohol 3 to 5 times, dissolved in a small amount of water, precipitated with alcohol, and then vacuum dried at 40 to 50° C. to obtain an amphiphilic copolymer; The molar ratio of acrylamide, N,N-dimethylacrylamide and N-acryloylmorpholine is (12 to 15): (3 to 4): (2 to 3); the weight of the initiator is 0.5% to 1% of the total weight of acrylamide, N,N-dimethylacrylamide and N-acryloylmorpholine; The preparation method of the modified nano silicon dioxide comprises the following steps: S01: dissolving 3-(methacryloyloxy)propyltrimethoxysilane in toluene, adding the mixture to the nano-silicon dioxide aqueous dispersion, ultrasonicating at 60-65°C for 45-60 minutes, stirring and reacting for 2-3 hours to obtain a modified nano-silicon dioxide dispersion; the pH of the nano-silicon dioxide aqueous dispersion is 4-5; S02 centrifuging the obtained modified nano-silicon dioxide dispersion, repeatedly washing with ethanol and then vacuum drying to obtain modified nano-silicon dioxide; The mass ratio of the 3-(methacryloyloxy)propyltrimethoxysilane to the nano-silicon dioxide is 1:(10-15).
2. A composite viscosity reducer according to claim 1, characterized in that: The preparation method of sodium fatty alcohol polyoxyethylene ether sulfonate comprises the following steps: S001 Add distilled water to a high temperature and high pressure reactor, then add sodium sulfate, sodium sulfite, sodium bisulfite and sodium bisulfate of fatty alcohol polyoxyethylene ether, stir evenly, and react for 6 to 8 hours; The materials in the S002 reactor are cooled to room temperature, and the reaction mixture is first dissolved with isopropanol, and dichloromethane is added to assist in dissolution, and then suction filtration, desalination, and solvent evaporation are performed in sequence to obtain sodium fatty alcohol polyoxyethylene ether sulfonate.
3. A composite viscosity reducer according to claim 2, characterized in that: The mass ratio of the sodium sulfite, sodium bisulfite and sodium bisulfate is (4 to 5):1:(0.05 to 0.1); the mass ratio of the sodium sulfite to sodium fatty alcohol polyoxyethylene ether sulfate is 1:(0.7 to 0.9).
4. A composite viscosity reducer according to claim 2, characterized in that: In step S001, the reaction temperature is 150-170°C, and the reaction pressure is 0.5-0.6MPa.
5. A composite viscosity reducer according to claim 1, characterized in that: The preparation method of the composite viscosity reducer comprises the following steps: Step 1: Dissolve the amphiphilic copolymer in a small amount of water, add modified nano-silica, and ultrasonicate at 40 ~ 60℃ for 30 ~ 45min; Step 2: Continue to add sodium fatty alcohol polyoxyethylene ether sulfonate and water, and stir evenly to obtain the composite viscosity reducer.
6. The oil recovery viscosity reduction process using a composite viscosity reducer according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) subjecting the composite viscosity reducer to hydrodynamic cavitation treatment for 1 to 3 times; (2) After the composite viscosity reducer treated by hydraulic cavitation is fully mixed with the crude oil, the hydraulic cavitation treatment is performed again for 5 to 10 times; The inlet temperature of the hydrodynamic cavitation treatment is 40-80°C, and the inlet pressure is 0.7-0.9MPa.
Citation Information
Patent Citations
Salt- and temperature-resistant emulsification viscosity reducer for heavy oil
CN102618239B
Nano SiO2 composite material thickened oil viscosity reducer and preparation method thereof
CN104327225A
Thickened oil in-situ viscosity reducer and preparation method thereof
CN116790237A